FUNCTIONS AND METHODS OF ORGANIZATION AND MANAGEMENT OF THE PROCESSES OF FORMATION OF FIRST AID SKILLS AMONG NON- MEDICAL STUDENTS (American Journal of Business Management, Economics and Banking, 2024)
The analysis of the consequences of industrial accidents and various disasters shows that one of the main causes of the negative impact of striking factors is a human being: workers are not able to apply in these situations the knowledge, skills and abilities in the field of protection from dangerous (emergency) situations received at the university. In other words, they have not developed perception, understanding and transformation of a specific situation in the system "man - danger" when performing their professional activity. Accordingly, readiness to work in suddenly changed conditions, in the development of extreme situations (fire, explosion, earthquake, flood, etc.), the ability to make and apply competent decisions, have become more and more demanded qualities of a graduate of the university [1].